(untitled) (Italian Journal of Public Health, 2006)
Background: Tobacco smoke is the main cause of mortality and morbidity in most industrialized countries. The aim of this research is to estimate the smoke attributable morbidity for Piedmont residents in the years 1997-2002 and the related costs for the regional health service, using as an indicator the number of hospital admissions caused by smoke and as an instrument the DRG rates. Methods: extraction of hospital admissions for smoking-related diseases; estimate of the proportion of hospital admittances attributable to smoking; estimate of the overall cost and the smoke attributable cost for each year. Results: The attributable proportion in men is clearly higher than in women. In men it decreases from 10.6% in 1997 to 8.2% in 2002, while values among women seem to have reached a plateau. The economic value of the attributable admissions, at current prices, shows a downward trend for men from 1997 to 2001 and an upward one in the year 2002, while for women the trend is fluctuating. Conclusions: This method demonstrates the following original features: we used metanalytic relative risks real prevalence data, considering a fifteen-year latency period between exposure and effect on health.The model that we developed adheres more adherent to the natural history of the disease and to the local health problem, giving us a useful tool for planning purposes.Furthermore, the economic estimate is made for each single DRG instead of applying medium rates for MDC, which happens more frequently at the national level.